Nuldrieënveertig : Ron Bernstein - Ton Boelhouwer - Jacqueline Böse - Paul Devens etc. (Maastricht : Stad Maastricht, 1994)
Bernstein, Ron ; Boelhouwer, Ton ; Böse, Jacqueline ; Devens, Paul ; de Graaf, Jaap ; Grunschel, Norbert ; Hermans, Benoît ; Kinoshita, Suchan ; Knappstein, Roel ; Kusters, Pascalle ; Meijers, Rik ; Meulendijks, Ingeborg ; Palemn, Désirée ; den Rooijen, Ines ; Schäfer, Anke ; Zeguers, Alex
Nuldrieënveertig : Ron Bernstein - Ton Boelhouwer - Jacqueline Böse - Paul Devens etc., Gebouw 'Landbouwbelang', Maastricht, 17.11.1994 - 22.01.1995
boek